An effective protocal for clonal propagation of "Proh Phu" (Caulokaempferia thailandica larsen).(Thai) - Bunnag, Sumontip; Theerakulpisut, Piyada; Maneerattanarungroj, Praweena; Tungpong, Duangkamol; Chunthapong, Jirapat (Asia-Pacific Journal of Science and Technology, 2017)
We have established an effective protocol for in vitro propagation of young buds of “Proh Phu” (Caulokaempferia thailandica), a rare plant species of Thailand. First, we investigated various conditions for surface sterilization and found that 10-min treatment with 0.01% (w/v) mercuric chloride was the most suitable condition for surface sterilization of this plant species. We then studied the effects of MS salt basal strengths and sucrose concentrations on survival rates and number of shoots and roots of explants. The results indicated that full-strength MS (1962) medium with 30 g/l sucrose and without coconut water was the most effective medium for culture initiation. Lastly, we investigated the effect of BA on direct organogenesis of C. thailandica. Fifteen shoots per explant and 92% survival rate were recorded after four-week culture on MS medium supplemented with 5 mg/l BA. Plantlets were successfully transferred to soil and acclimatized in a growth chamber. Morphologically normal plants were obtained from 2-4 month potting. To our knowledge, this work represents the first successful in vitro clonal propagation of C. thailandica, with promising implications in large-scale propagation and ex situ conservation of this rare plant.